Psychology of Labor Safety in Industrial Enterprises - B. O’., Karimov; L. M., Eshmuxamedov (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides information on the history of the emergence of safety psychology as a science, its content, and its role in preventing accidents in production. The results of research on mental characteristics, mental processes and mental state, their impact on labor safety, conditions for safe conduct of work depending on a person's character, psychological resistance of a person and psychological causes of accidents, including psychological reasons that make a person consciously allow it, are covered.